Draft Annual Plan 1988-89 Part - II: Plan Proposals in Detail Union Territory of Daman and Diu - Planning Commission (Planning Commission, 1987)
The main objective of the scheme is to increase food production by bringing more area under cultivation of high yielding varieties by replacing the traditional low yielding varieties of crops. Under this programme, certified seed of high yielding varieties of paddy and other crops will be procured, produced, multiplied and distributed to the farmers by way of extensive high yielding varieties programme. The research trials of newly released high yielding varieties to test their adaptability to the soil and climatic conditions of this region will also be made.
Directorate of Planning, Statistics and Evaluation, Government of Goa